KONSELING ISLAMI TEKNIK COGNITIVE DEFUSION UNTUK MENANGANI OVERTHINKING KARIR SISWA SMAN 1 DAYEUHKOLOT BANDUNG - Elriyani, Susi; Miharja, Sugandi; Kurnia, Aam (UIN Sunan Kalijaga Yogyakarta, 2025)
The phenomenon of overthinking has now become a real challenge experienced by many students, especially in facing the uncertainty of the future and career choices. At SMAN 1 Dayeuhkolot, it was found that most students felt excessive anxiety, doubt, and difficulty in designing the right career steps. This not only impacts their emotional condition, but also interferes with the learning process and decision-making. Departing from this anxiety, this study was conducted to test the effectiveness of the Cognitive Defusion technique in Islamic counseling as one approach to dealing with career overthinking in students. The method used is a quantitative approach with a one group pretest-posttest experimental design. Data were collected through questionnaires, interviews, and observations, and analyzed using the Wilcoxon test through SPSS software. This study was conducted on grade XI students who had previously been identified as experiencing overthinking related to careers. The results of the study showed that the Cognitive Defusion technique in Islamic counseling was effective in reducing the level of career overthinking in students. Students became better able to recognize and free themselves from negative thoughts, and had a clearer view of their career future. This approach not only touches on psychological aspects, but also spiritual ones, thus providing a more comprehensive impact on students' inner peace and future planning. Keywords: Overthinking, Career, Cognitive Defusion, Islamic Counseling, High School Students